Paradigm warriors: Advancing a radical ecosystems view of collective leadership from an Indigenous Māori perspective. (April 2020) - Spiller, Chellie; Maunganui Wolfgramm, Rachel; Henry, Ella; Pouwhare, Robert
Collective leadership is cast as a new and emerging paradigm. However, for many Indigenous communities, collective leadership has been a way of life through the millennia. Where mainstream models of collective leadership focus on what people do, think, and feel in the here and now, we argue such an approach ignores contributions of other generations. The Māori ecosystems view set out in this article positions a revolutionary departure from previous work on collective leadership because of the extraordinary set of relationships it encompasses, including those across generations and across living and non-living entities. Meeting this special issue's call for innovative research methodologies, our work is informed by the ancient practice of wānanga, which challenges secular, reductionist, quantitative research. Wānanga traverses time and space and involves a quality of consciousness that brings forth an integrated collective intelligence. Inquiring into three watershed leadership moments, we show that collective Māori leadership is an ecosystem held together by activating a knowledge code, cultivating ties of affection, and working the tensions. Unlike the 'new broom sweeps clean' approach where incoming leaders tend to discard the work of predecessors, true collective leadership is an integrated ecosystem sustained from one generation of leadership to the next.